Evaluation of Annual Clover Ecotypes by Using Drought Tolerance Indices - Sh. Nikou; M. Pouryousef Miandoab; A. Hassanzadeh Gorttape (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī, 2014)
To evaluate clover ecotypes by using  drought tolerance indices, 17 annual clover ecotypes were tested in a split-plot experiment by using randomized complete  block design with three replications, under two irrigated and rain-fed conditions in the Saatlo Research Station in Urmia, Iran. In this study, based on the dry matter yield in stressed (Ys) and non-stressed (Yp) conditions, quantitative values of drought tolerance indices of mean productivity index (MP), tolerance index (TOL), geometric mean productivity index (GMP), harmonic mean index (HM), stress susceptibility index (SSI), and stress tolerance index (STI) were calculated. There was a significant difference among the ecotypes as to their yields under irrigated and rain-fed conditions, which indicated the existence of genetic diversity and the possibility of selection for drought tolerance and using them in breeding programs for further genetic. The correlations among drought indices and Yp and Ys showed that MP, GMP, HM, and STI were highly correlated with Yp and Ys. Cluster analysis categorized tolerant ecotypes No. 11, 2, 13, 8 and 10 in the same group and the others in the sensitive one. Based on the values of indices and higher dry matter yield, in both stress and non-stress conditions, ecotype No. 11 (T.resupinatum L.) was recognized to be as the most tolerant ecotype against drought.